Danny Sullivan at the state high school swimming meet at Wake Forest College, 1964. - (:unkn) unknown (Forsyth County Public Library)
WSJ 3-15-64 p.1B.
Danny Sullivan at the state high school swimming meet at Wake Forest College, 1964. Danny won the state diving championship.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth